General infection prevention, mitigation, and control procedures implemented in the university education during the COVID-19 pandemic to achieve classroom attendance: a successful community case study - Monge, Diana; Gallego-Gil, Ana; Neria, Fernando; Canellas, Soledad; Caballero, Fernando; Díaz de Bustamante, Ana; Samper, Mónica (Frontiers in Public Health, 2024)
Introduction: The COVID-19 pandemic entailed confinement and elimination of face-to-face university classes in Spain. The Francisco de Vitoria University in Madrid (UFV by its Spanish acronym) implemented risk management systems to enable on-campus university activity to avoid a negative impact on students, teachers, and faculties. Methods: A tracking/registry system was implemented to collect data, identify COVID-related cases, implement containment measures, and do follow-up in the UFV community (administration/services personnel [ASP], teaching/research personnel [TRP], and students), from Sep-2020 to Apr-2022. In addition, a prevention plan was implemented on campus to avoid COVID-19 spreading. Satisfaction with these measures was assessed through an online questionnaire. Results: A total of 7,165 suspected COVID cases (84.7% students, 7.7% ASP, 6.5% TRP) were tracked (62.5% female, mean age (±SD) 24.8 years (±9.2 years)), and 45% of them confirmed (82% symptomatic/16% asymptomatic), being the student group that with the highest percentage (38.3% total tracked cases). The source of infection was identified in 50.6% of the confirmed cases (90.2% located off-campus). Nineteen COVID-19 outbreaks were registered (inside-10/outside-9). COVID-19 incidence rates were similar or lower than those reported in the Community of Madrid, except in the sixth wave. The degree of satisfaction (scale 1-6) with the implemented measures was high (scores 4.48–5.44). Conclusions: During the COVID-19 pandemic, UFV control measures, periodic monitoring, and the effectiveness of the tracking system have contributed to maintaining classroom teaching, guaranteeing health and safety. UFV has adapted to a new reality as an example of good practice for future pandemics or emergency situations.